Occurrence of protozoa and soil transmitted helminth (STH) in human feces used as manure in agriculture - Akter, Tamanna; Musa, Sharmin; Khanum, Hamida (Dhaka University Journal of Biological Sciences, 2015)
To assess the health risk association of soil contamination with parasite, a total number of 168 faecally contaminated night soil was studied. The presence of four protozoan parasites, viz. Cryptosporidium sp., Entamoeba histolytica, Giardia sp., Trichomonas hominis and eight different helminthes, viz. Diphyllobothrium latum, Hymenolepis sp., Taenia sp., Ascaris lumbricoides, Ancylostoma duodenale, Enterobius vermicularis, Strongyloides stercolaris and Trichuris trichiura were identified. Among the protozoans, Giardia sp. was the highest (46.43%) and most abundant (339.87 ± 17.01 cysts/g); among helminthes the prevalence of Ascaris lumbricoides was the highest (80.95%) and Strongyloides stercoralis was mostly abundant (409.31 ± 47.53 larvae/g). Highest percentage of mild infections was found in Giardia sp. (43.45), and lowest in Trichomonas hominis (8.33). Whereas, among helminthes, highest percentage (64.29), of mild infections was found in Ascaris lumbricoides and lowest (11.90) in Taenia. In case of protozoa, moderate infection found in Giardia sp. (2.98%) and Entamoeba histolytica (3.57%), but in case of helminth only Ascaris lumbricoides showed moderate infections (16.67%). Dhaka Univ. J. Biol. Sci. 24(2): 161-168, 2015 (July)